Gpm6b deficiency impairs sensorimotor gating and modulates the behavioral response to a 5-HT2A/C receptor agonist - Dere, Ekrem; Winkler, Daniela; Ritter, Caroline; Ronnenberg, Anja; Poggi, Giulia; Patzig, Julia; Gernert, Manuela; Müller, Christian; Nave, Klaus-Armin; Ehrenreich, Hannelore; Werner, Hauke B. (Behavioural Brain Research, 2015)
The neuronal tetraspan proteins, M6A (Gpm6a) and M6B (Gpm6b), belong to the family of proteolipids that are widely expressed in the brain. We recently reported Gpm6a deficiency as a monogenetic cause of claustrophobia in mice. Its homolog proteolipid, Gpm6b, is ubiquitously expressed in neurons and oligodendrocytes. Gpm6b is involved in neuronal differentiation and myelination. It interacts with the N-terminal domain of the serotonin transporter (SERT) and decreases cell-surface expression of SERT. In the present study, we employed Gpm6b null mutant mice (Gpm6b(-/-)) to search for behavioral functions of Gpm6b. We studied male and female Gpm6b(-/-) mice and their wild-type (WT, Gpm6b(+/+)) littermates in an extensive behavioral test battery. Additionally, we investigated whether Gpm6b(-/-) mice exhibit changes in the behavioral response to a 5-HT2A/C receptor agonist. We found that Gpm6b(-/-) mice display completely normal sensory and motor functions, cognition, as well as social and emotionality-like (anxiety, depression) behaviors. On top of this inconspicuous behavioral profile, Gpm6b(-/-) mice of both genders exhibit a selective impairment in prepulse inhibition of the acoustic startle response. Furthermore, in contrast to WT mice that show the typical locomotion suppression and increase in grooming activity after intraperitoneal administration of DOI [(±)-1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane hydrochloride], Gpm6b(-/-) mice demonstrate a blunted behavioral response to this 5-HT2A/C receptor agonist. To conclude, Gpm6b deficiency impairs sensorimotor gating and modulates the behavioral response to a serotonergic challenge.
EVALuna2:23737